Pengaruh Media Pembelajaran Flashcard Terhadap Kemampuan Membaca Huruf Hijaiyah Pada Anak di Majlis Ta’lim Nurul Ilmi Citeureup Kabupaten Bogor - Sabrina, Neng; Edy (Dakwatussifa: Journal of Da'wah and Communication, 2024)
Parents have the responsibility to facilitate the reading of the hijaiyah letters they don't understand and find it difficult to memorize hijaiyah letters for children and for children religious noble character. The time allocation in the ta'lim majlis is only 2 hours a week, Therefore, increasing the reading of Iqra' and the Al-Qur'an in children is wrong One effort parents make is to ensure that children are diligent in studying reading iqra' and other religious knowledge. Which aims other than to improve read Iqra' but also the Koran and to increase faith, understanding, and experience of Islamic teachings. So that children are motivated to learn, that's why we as a teacher at the majlis Ta'lim Nurul Ilmi improves learning methods, namely use Flashcard learning media so that children are enthusiastic and enthusiastic the learning. The purpose of this research is to find out the influence of the media Flashcard Learning on the Ability to Read Hijaiyah Letters in Children Majlis Ta'lim Nurul Ilmi Citeureup, Bogor Regency.